Adverb og adverbialer: En forsømt ordklasse i ordbøkene - Jónsson, Jón Hilmar (Nordiske Studier i Leksikografi, 2012)
In most traditional dictionaries the status of adverbs and adverbials is weak compared to other word classes. This applies to the selection of lemmas where adverbs seldom have high priority, partly because of the dominance of adjective lemmas of the same word stem. It also applies to the status of many multi-word adverbials which can be difficult to detect within the entries of nouns, verbs and adjectives, especially when the adverbial has an independent meaning. Syntactically, adverbs and adverbials are most closely related to verbs but their occurrence and description in verb entries is inevitably limited because of the condensation of the dictionary text. In electronic dictionaries adverbs and adverbials can assume a stronger position. Multi-word adverbials, like other multi-word units, can be directly searchable and even have lemma status on the same basis as single-word lemmas. Grammatical tagging of such lemmas also allows search and classification independent of their lexical representation. Grammatical sorting and classification also facilitates the semantic analysis, with regard to synonym and antonym relations and to the grouping of related lemmas in larger semantic fields. The article discusses this theme with reference to Icelandic dictionary material and an ongoing lexicographical project.